Simulación del transporte de calor en nanoestructuras de silicio - Mancardo Viotti, Agustin Matias; Bea, Edgar Alejandro; Carusela, María Florencia; Monastra, Alejandro Gabriel; Soba, Alejandro (Asociación Argentina de Mecánica Computacional, 2018)
Fil: Mancardo Viotti, Agustin Matias. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de General Sarmiento. Instituto de Ciencias; Argentina